The Use of Reading Aloud in Teaching Reading Comprehension - Anum Sahara (Research in English and Education Journal, 2018)
This quantitative study was aimed to find out whether there is a significant effect on students achievement after applying reading aloud technique for students’ reading comprehension of the second grade at SMP Negeri 8 Banda Aceh. The pre-experimental research with one group pre-test post-test design was undertaken to see achievement of the use of reading aloud technique. This research utilized pre-test and post-tests to collect the data. The class VIII-5 of junior high school was chosen as the sample in this study to receive treatment for three meetings. The data was then analyzed by using independent t-test. The calculation showed that the post-test score is 45 was higher than the pre-test’ score, it was 36 with the significant standard 0.030 0.05. The result of the research showed that Detail Information and Vocabulary aspects were increased slightly after being taught by using reading aloud technique. Although the improvement only on those two aspects of reading, it is still recomended this technique to be used in teaching reading.